2018
DOI: 10.1002/lsm.22811
|View full text |Cite
|
Sign up to set email alerts
|

A customized approach for arm fat reduction using cryolipolysis

Abstract: This study documents the first reported customized approach for assessment and treatment of arm fat using a small or medium cup applicator with varied applicator placement. By incorporating one or two treatment cycles per arm in a single session, the issue of variable fat distribution in people's arms can be addressed. This approach was shown to be a safe and effective way to reduce unwanted arm fat with high patient satisfaction. Lasers Surg. Med. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
(46 reference statements)
1
12
1
Order By: Relevance
“…This result is similar to that reported by Lee et al (2016) who found a reduction of 15.3% in adipose tissue among seven subjects treated once 18 . Arm fat reduction through cryolipolysis technique was also previously assessed by other authors and significant results are reported 19,20 …”
Section: Discussionsupporting
confidence: 91%
“…This result is similar to that reported by Lee et al (2016) who found a reduction of 15.3% in adipose tissue among seven subjects treated once 18 . Arm fat reduction through cryolipolysis technique was also previously assessed by other authors and significant results are reported 19,20 …”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the arm procedures only deal with sagging skin and excess fat, while neglecting the role of underlying muscles in the resulting overall appearance. Currently, there are only moderately effective non-invasive arm lifting alternatives such as cryolipolysis 6,7 or radiofrequency 8,9 devices, which focus on skin tightening and reducing arm fat while the muscles remain untouched. However, to maximize the treatment outcome and results it is necessary to take into account both muscle and fat.…”
Section: Introduction Imentioning
confidence: 99%
“…Vibration from PAL infiltration of tumescent solution can be a helpful sensory distraction for patients having surgery under local anesthesia. Furthermore, PAL allows for even infiltration throughout tissues even in presence of significant scarring due to previous liposuction or other non-invasive fat reduction procedures such as cryolipolysis or deoxycholic acid injections [23,24]. A UAL probe of 3 mm is used for fat emulsification followed by lipoaspiration with SAL, again using a 3 mm cannula.…”
Section: Vaser Liposuctionmentioning
confidence: 99%
“…Applications of cryolipolysis in the extremities is generally limited as most patients require contouring of the entire upper length of the extremities with skin quality frequently also needing to be addressed. Rivers [23] has described the use of multiple coupled cryolipolysis applicators to broaden inclusivity of patients to those with more fatty excess, but this technique can be costly for patients. We reserve cryolipolysis for treatment of patients who seek only non-invasive treatments, are young with good skin quality and elasticity, and have mild localized areas of adipose excess in the upper arm or anterior axillary region.…”
Section: Cryolipolysismentioning
confidence: 99%